Genomic structure of a crossbred Landrace pig population - Joaquim, Letícia Borges [UNESP]; Chud, Tatiane Cristina Seleguim [UNESP]; Marchesi, Jorge Augusto Petroli [UNESP]; Savegnago, Rodrigo Pelicioni [UNESP]; Buzanskas, Marcos Eli; Zanella, Ricardo; Cantão, Mauricio Egidio; Peixoto, Jane Oliveira; Ledur, Mônica Correa; Irgang, Renato; Munari, Danísio Prado [UNESP] (Public Library of Science (PLoS), 2019)
Single nucleotide polymorphism (SNP) markers are used to study population structure and conservation genetics, which permits assessing similarities regarding the linkage disequilibrium and information about the relationship among individuals. To investigate the population genomic structure of 300 females and 25 males from a commercial maternal pig line we analyzed linkage disequilibrium extent, inbreeding coefficients using genomic and conventional pedigree data, and population stratification. The average linkage disequilibrium (r2) was 0.291 ± 0.312 for all adjacent SNPs, distancing less than 100 Kb (kilobase) between markers. The average inbreeding coefficients obtained from runs of homozygosity (ROH) and pedigree analyses were 0.119 and 0.0001, respectively. Low correlation was observed between the inbreeding coefficients possibly as a result of genetic recombination effect accounted for the ROH estimates or caused by pedigree identification errors. A large number of long ROHs might indicate recent inbreeding events in the studied population. A total of 36 homozygous segments were found in more than 30% of the population and these ROH harbor genes associated with reproductive traits. The population stratification analysis indicated that this population was possibly originated from two distinct populations, which is a result from crossings between the eastern and western breeds used in the formation of the line. Our findings provide support to understand the genetic structure of swine populations and may assist breeding companies to avoid a high level of inbreeding coefficients to maintain genetic diversity, showing the effectiveness of using genomewide SNP information for quantifying inbreeding when the pedigree was incomplete or incorrect.